PENGELOLAAN PUPUK TERPADU DALAM UPAYA MENINGKATKAN HASIL JAGUNG MANIS DAN KESUBURAN LAHAN PADA SISTEM TANAM JAJAR LEGOWO 2:1 - Pamandungan, Yefta; Runtunuwu, David S.; Mamarimbing, Rinny; Najoan, Jemmy (Universitas Sam Ratulangi, 2016)
ABSTRACT This research aims to study the increase of the yields of sweet corn and soil fertility by applying integrated fertilizers management system in Jajar Legowo 2:1 planting system. The results of this research show that providing the 25% inorganic fertilizers plus 75% organic fertilizers as treatment has given better result for the yields of sweet corn than providing 100% inorganic fertilizers or 100% organic fertilizers as treatment. Chemical properties of the soil before and after the treatment of fertilizers, it is found out that the contents of C-Organic, N of soil, and K2O of the researched soil are categorized as low to very low. However, it is found out that the available content of P2O5 has increased by 4.29 ppm through the 25% inorganic fertilizers plus 75% organic fertilizers as treatment and has increased by 1.73 ppm through the 100% organic fertilizers as treatment. Keywords: integrated fertilizer management, sweet corn, jajar legowo